IMPLEMENTASI NILAI-NILAI PANCASILA MELALUI BUDAYA KAMPUS DI ERA DIGITAL Di LINGKUNGAN STTI BONTANG - Irianto (Manajemen Pendidikan Program Doktor, 2025)
This study explores how the values of Pancasila are implemented in STTI Bontang in the digital era. Using a multiple-case study approach, we conducted online interviews, participatory observations, and document analysis. The results indicate that Pancasila values are reflected in campus life, supported by digital technology such as social media and online learning. Changes are evident in the academic atmosphere and campus technology. In conclusion, STTI Bontang has successfully integrated Pancasila into the digital campus culture, creating a collaborative and innovative environment. The findings emphasize the importance of national values in higher education in the digital era.